Reflections on a Proposed Theory of Reservation-Dwelling American Indian Alcohol Use Comment on Spillane and Smith (2007) . [article]. - Beals, Janette
In their recent article, N. Spillane and G. Smith (2007) suggested that reservation-dwelling American Indians have higher rates of problem drinking than do either non-America Indians or those American Indians living in nonreservation settings. These authors. These authors further argued that problematic alcohol use patterns in reservation communities are due to the lack of contingencies between drinking and " standard life reinforcers" (SLRs), such as employment, housing, education, and health care. These comments presents evidence that these arguments were based on a partial review if the literature. Weaknesses on the application of SLR constructs to American Indian reservation communities are identified as is the need for culturally contextualized empirical evidence supporting this theory and its application. Cautionary notes are offered about hte development of literature reviews, theoretical framework, and policy recommendations for American Indians communities. -- (from the author)
Keywords: American Indians; Alcohol; Problem drinking; Reservation